Understanding the patterns of fish and seafood consumption and its nutritional roles among a Malaysian population to inform sustainable development - Goh, Ee Von; Azam Ali, Susan; Roy Mitra, Soma; McCullough, Fiona (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2021)
This study was designed to generate baseline data of the fish and seafood consumption pattern among major ethnics in urban, rural, and coastal regions of Peninsular Malaysia. A food frequency questionnaire was adapted and administered on healthy adult participants above 18 years. Fish and seafood is the prime animal protein source in Malaysian diet, comprising about one-third of total animal protein consumed. Average per capita fish and seafood consumption is 44.53kg/year, with higher levels observed in coastal (51.9kg/year) and rural (51.8kg/year) than urban areas (36.9kg/year). While the fish and seafood intake is relatively high, the total polyunsaturated fatty acids intake is borderline low. Despite cross- cultural and regional variations, there is a great overall preference for wild caught marine pelagic fishes. The demand has to be satisfied by imports, even after increasing local fishing effort. The data are beneficial for sustainability assessment and to inform policies for a sustainable food future